Perspektif Teori Komunikasi Behaviorisme Oleh John Broadus Watson - Khumaira, Asyifa; Gabriella, Fenika; Charis, Jessica Caroline; Setijadi , Naniek N. (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In the last few decades, communication technology has undergone rapid advancements that significantly impact the consumption patterns of digital media in modern society. This research employs the behavioral communication theory perspective developed by John Broadus Watson to delve deeper into the influence of communication technology on the consumption patterns of digital media among modern society. The research findings highlight that communication technology plays a crucial role in shaping the consumption patterns of digital media in modern society. One notable impact is the increased time spent consuming digital media content. The primary driving factor for this increase is the stimulus provided by the availability of diverse and engaging digital content. Additionally, the shift in the types of content consumed is also a result of the influence of communication technology. Modern society tends to respond to stimuli such as the need for information and education by consuming relevant and beneficial digital media content. Furthermore, the research notes an increase in social interaction through digital media as a consequence of technological advancements in communication. This can be explained as a response to the societal need to stay connected with others. With the existence of digital media platforms, social interaction is no longer confined by geographical limitations, allowing individuals to communicate and share experiences virtually. Consequently, it can be concluded that communication technology plays a central role in transforming the consumption patterns of digital media in modern society. The increased consumption time, changes in content types, and the heightened social interaction through digital media serve as tangible evidence of the positive and transformative impact of communication technology development in meeting the demands and needs of modern society.